How do households utilize banking services and what are the determinants of it? An empirical analysis from the rural and tribal areas of an eastern Indian state. Issue 2 (1st October 2020) - Ray, Dipti; Rout, Himanshu Sekhar; Ray, Pritee
Abstract : Accessibility and utilization of banking services are the key elements of financial inclusion. Accessibility is the gateway, whereas utilization actually matters in deriving the positive impact of financial inclusion. Plethora of studies have covered the accessibility dimension; however, we found a lack of empirical analysis of the utilization of it. This paper analyses the utilization dimension of financial inclusion using empirical evidence from the rural and tribal regions of an eastern Indian State, that is, the State of Odisha, which is among the low financially included regions of India. The paper explores the purpose/pattern, depth and frequency of utilization of formal financial services using primary data and develops empirical models explaining the demand and supply‐side determinants. The findings include, the utilization of account for saving and borrowing is not satisfactory. Similarly, the depth of account use is limited due to lack of ICT knowledge. The use of bank accounts for the financial transaction is mainly performed to receive direct benefit transfers and NREGS payments rather than savings, credit and insurance purposes. The policymakers can be benefited from this research by understanding the determinants of financial utilization at the grassroots level and could take corrective measures to promote utilization.